2020
DOI: 10.1002/art.41210
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Cartilage Microbial DNA Signatures and Associations With Knee and Hip Osteoarthritis

Abstract: ObjectiveAlterations of the gut microbiota have been implicated in many forms of arthritis, but an examination of cartilage microbial patterns has not been performed. This study was undertaken to characterize the microbial DNA profile of articular cartilage and determine changes associated with osteoarthritis (OA).MethodsWe performed 16S ribosomal RNA gene deep sequencing on eroded and intact cartilage samples from knee OA patients (n = 21 eroded and 21 intact samples) and hip OA patients (n = 34 eroded and 33… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 53 publications
5
55
0
Order By: Relevance
“…Lactobacillus has been shown to be depleted within the gut during mouse aging [53], a known risk factor for OA development. These findings align with our previous work which identified Lactobacillales DNA as characteristic of both disease-free human control and OA-protected MRL cartilage [54]. Similarly, we found family Clostridiaceae within cecal microbiota to be highly correlated with ear wound healing, and we previously identified this clade as associated with disease-free human cartilage.…”
Section: Plos Onesupporting
confidence: 92%
“…Lactobacillus has been shown to be depleted within the gut during mouse aging [53], a known risk factor for OA development. These findings align with our previous work which identified Lactobacillales DNA as characteristic of both disease-free human control and OA-protected MRL cartilage [54]. Similarly, we found family Clostridiaceae within cecal microbiota to be highly correlated with ear wound healing, and we previously identified this clade as associated with disease-free human cartilage.…”
Section: Plos Onesupporting
confidence: 92%
“…Lactobacillus has been shown to be depleted within the gut during mouse aging [49], a known risk factor for OA development. These findings align with our previous work which identified Lactobacillales DNA as characteristic of both disease-free human control and OA-protected MRL cartilage [50]. Similarly, we found family Clostridiaceae within cecal microbiota to be highly correlated with ear wound healing, and we previously identified this clade as associated with disease-free human cartilage.…”
Section: Discussionsupporting
confidence: 92%
“…Our results indicate that future studies of the intra-articular microbiome should be performed from different geographical locations in order to comprehensively characterize the various microbial compositions that are involved in the initiation and progression of OA. In addition, in light of a report by Dunn et al that identified a microbial DNA signature in human knee and hip cartilage [ 58 ], future work could include assessment of the synergistic role of the cartilage and synovial microbiomes in OA development. Lastly, the concurrent assessment of the gut, blood and intra-articular microbiome would support the hypothesis that a “leaky” gut allows for microbial migration from the gut to the joint, contributing to OA pathogenesis.…”
Section: Discussionmentioning
confidence: 99%